Pemetaan Pola Sebaran Sampah Berdasarkan Jenis di Wilayah Pesisir Pantai Desa Rumah Tiga Kecamatan Teluk Ambon Kota Ambon - Surita Ungalesi; Daniel Anthoni Sihasale; Mohammad Amin Lasaiba (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Waste problems in coastal areas are a serious issue affecting environmental quality and ecosystem sustainability. This study aims to identify and map waste distribution patterns by type along the coastal area of Rumah Tiga Village, Teluk Ambon District, Ambon City. The research employed a field survey with a line transect approach, supported by GPS-based spatial recording and GIS analysis. The findings reveal that waste distribution is strongly influenced by community activities, particularly around markets and residential zones, with inorganic waste dominating—soft plastics accounting for 33% and hard plastics for 17%. Meanwhile, open coastal areas were mainly filled with natural debris such as wood and leaves. These results confirm that most coastal waste originates from land-based sources rather than marine input. This research contributes essential spatial evidence for formulating more effective waste management policies, raising public awareness, and encouraging multi-stakeholder engagement in preserving coastal ecosystems. Recommendations emphasize strengthening local regulations, implementing community-based management systems, and establishing continuous educational programs at the community level